Heterogeneous carbon dioxide reduction reaction by cobalt complexes of 4′,4′′′-disubstituted derivatives of quinquepyridine immobilized on carbon black - Reddu, Vikas (2022)
Molecular catalysts represent an excellent class of materials for carbon dioxide reduction that can perform with superior selectivity and allow for the molecular-level tuning of their structure-performance relationship. In this study, three quinquepyridine-based cobalt complexes were synthesized with different types of functional group (-N(CH3)2, -NO2, -H) substitutions allowing us to manipulate the electronic field around the metal center due to their varying electron donating and withdrawing tendencies. These were heterogenized onto carbon black enabling them to perform in near neutral aqueous conditions (pH = 6.8). At an optimized catalyst loading of ~100 μg cm−2, dimethylamine- and nitro-substituted complexes outperformed the unsubstituted complex, wherein, dimethylamine substituted complex attained nearly 100% faradaic efficiency towards CO formation at a low overpotential (η) of 0.59 V (-0.7 V vs. RHE) and achieved a current density (j) of ~4.3 mA cm−2. It maintained its robust performance towards the formation of CO over a wide range of overpotential while suppressing the competitive hydrogen evolution reaction. This enhanced activity compared to the unsubstituted complex was attributed to the effects exerted by the functional groups at the molecular level.